Bridging Research and Practice: Swiss Olympic’s Approach to Sports Science and Innovation - Sarah Geboltsberger (Current Issues in Sport Science)
Swiss Olympic is the umbrella organisation for Swiss sport and supports the national sports federations at various levels, increasingly also in the area of (sports) science. Research, development and innovation are key factors in remaining competitive in the international sports competition.